Whitehead and God : prolegomena to theological reconstruction - Wilmot, Laurence F., 1907- (desLibris. Books collection., 1979)
This book is intended as a contribution towards the renewal of theological discourse in the final quarter of the twentieth century. It presents the findings from personal research into the development of the concept of God in the philosophy of Alfred North Whitehead, and the application of his conceptual tools in a re-examination of the writings of some fourth-century Christian theologians in their efforts to provide answers to the problems posed for the Church by Arianism. The research was prompted by Whitehead's recommendations addressed to theologians in Adventures of Ideas.